Between philosophy and art: A collaboration at The Lock-Up, Newcastle. Issue 2 (1st September 2016) - McMahon, Jennifer A.; Coleman, Elizabeth Burns; Macarthur, David; Phillips, James; Sturmer, Daniel Von
At The Lock-Up in Newcastle one weekend in September 2015, a group of artists, musicians and performers, performed to an audience which included philosopher commentators. The idea was to look for points of intersection, interface or divergence between art and philosophy. However, what we found was that the commentators were not engaged in analysing what was simply given them, but instead actively constructing the meaning they would ascribe to the work. As such they were co-creators. The objective of this report of the event is to establish a basis for more collaboration between art and philosophy in the future on the assumption that interdisciplinarity reveals possibilities and perspectives masked by the general insularity of well-established disciplines.